SLGC: A fast point-in-area algorithm based on scan-line algorithm and grid compression - Kunhui Lin; Yating Chen; Ming Qiu; Ming Zeng; Wei Huang (2016 11th International Conference on Computer Science & Education (ICCSE), 2016)
It is a common demand to solve regional limited problem in Internet of Vehicles (IoV) system with restricted time and storage requirements. In this paper, we present a fast point-in-area algorithm to tackle this problem. In the preprocessing phase, non-uniform grids are constructed by length thresholds and each row of the grids is viewed as a scan-line. The scan-lines scan area from top to bottom to find out whether a cell is inside or outside of the area. The algorithm locates the cells that contains the test point, and then determine the test point is inside or outside the area. Our method is used in an IoV system to supervise whether a truck is out of limited area or drive into restricted area and alarms correspondingly. Experimental results show that our method is faster than other point-in-polygon algorithms with less storage assumption. It is even faster than the method of convex decomposition, which has the linear time complexity 0(N) for point-in-polygon tests.